Recovery of sodium from alumina-extracted fly ash using concentrated sodium carbonate solution - Wang Z.; Zheng S.; Ma S.; Ding J.; Wang X. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A novel method for the recovery of sodium from alumina-extracted fly ash (AEFA) using concentrated Na2CO3 solution is presented. Sodium was efficiently extracted from AEFA, which was mainly composed of NaCaHSiO4. The factors influencing the process were systematically investigated, and the optimal conditions were determined to be: reaction temperature = 180°C, Na2CO3 concentration = 170 g/L, liquid-to-solid ratio = 10 mL/g, and reaction time = 2 h. Under optimal conditions, a low Na2O content of 1.02 wt% of the products, with Na2O extraction rate of 93.79% was achieved. The results indicated that this process was more effective than the recovery of sodium from AEFA using a dilute NaOH solution. Furthermore, this process avoided the production of a dilute NaOH solution, therefore lowering the energy consumption during the concentration and recycling of sodium, when compared with the NaOH-based route. Therefore, the recovery of sodium from AEFA using concentrated Na2CO3 solution is more suitable for use in industrial applications.